Exploration of pain in children on antiretroviral treatment in a regional hospital in South Africa - M. Azam; L. Campbell; A. Ross (South African Family Practice)
Background: Patients with human immunodeficiency virus (HIV) disease on antiretroviral therapy (ART) may experience pain for a variety of reasons, including the effects of the virus itself, associated opportunistic infections and the ART. Studies indicate that pain in adults on ART is frequent, can be severe, and is often undertreated. This study sought to explore the experience, and the prevalence of pain in young children aged 3-13 years on ART.